The Connection Between the Science of Mathematics and the Science of Logic (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The aim of the research is to study the relationship between logic and mathematics in the structure of axiomatized and formalized scientific theories. The object of the research is the explication of this relationship and its explanation. The subject of the research is syntactic and semantic views on the structure of scientific theories; the relationship between logic and mathematics in them has not been studied in detail.